PRICE EQUIVALENT IMPACTS OF THE DDA IN THE KOREAN RAW-MILK MARKET - 전상곤 (한국농촌경제연구원, 2009)
This study estimates the potential impacts of the Doha Development Agenda (DDA) on the Korean raw-milk market. The DDA has not reached an agreement yet. Although there are different attitudes about several issues such as Special Safeguard Mechanism (SSM), Sensitive Products (SP), and Tariff Rate Quota (TRQ) creation, WTO member countries have reached an agreement for major issues of the modalities in the DDA. Hence, this study estimates the impacts of the DDA that will finally reach an agreement sooner or later. For estimating the impacts of the DDA, this study makes a dairy trade model for the Korean dairy industry and measures the impacts of the DDA in terms of raw-milk price for fluid use incurred by further tariff cuts in the Korean dairy market by the DDA. This study considers several scenarios because the status of Korea is not settled yet and a country can select dairy products as sensitive products, special products, or general products and a country can select different options in each category. The results of this study can be used for preparing policies for subsidizing the domestic raw-milk producers to rebalance their loss in the raw-milk market incurred by the DDA.
Keywords: DDA; dairy; milk; tariff; price equivalent; DDA; dairy; milk; tariff; price equivalent